Personal insolvency dynamics in Germany and the UK: A SUR-TAR approach - Nadja König (Hamburg University, Department Socioeconomics, 2016)
This paper analyses the dynamics of personal insolvencies in Germany and the UK, focusing on the recent recession. These countries are particularly interesting as they are both member countries of the European Union, yet have completely different approaches to deal with overindebted individuals. In Germany unfortunate households who file on their debt are required to undergo a relatively long restructuring period until they eventually receive debt relief, whereas British debtors can choose proceeding out of many alternatives to manage their debt. Even under the official bankruptcy option, debt gets discharged relatively fast. In line with their different insolvency procedures, the two countries also represent two different financial systems: the German system is rather bank-based and the UK system rather market-based. The underlying financial systems already point to different patterns of lending across countries and hence, also to different structures of debt. Specifically, we are interested in the dynamics of petitions and actual insolvencies during the crisis as well as their reaction to exogeneous macroeconomic and financial conditions. The findings suggest that insolvencies are more persistent in the UK than in Germany, i.e. after an external shock it takes longer for insolvencies to return to their previous level in the UK. In both countries, the recent recession has no effect on petitions to default, but it has an effect on actual insolvencies in the UK suggesting that debtors rather opted for official procedures during the recession.
Keywords: E44; G01; G21; K49; 330; Private Household Debt; Personal Insolvency Laws; Recessions